2021
DOI: 10.1177/10105395211022944
|View full text |Cite
|
Sign up to set email alerts
|

Young Pacific Male Athletes’ Attitudes Toward Mental Health Help-Seeking in Aotearoa New Zealand

Abstract: Mental health is a pressing issue among Pacific communities in Aotearoa New Zealand, particularly among young Pacific men who have a high incidence of suicide deaths and reduced access to mental health services. Young Pacific men are heavily represented in professional sports, and despite limited empirical evidence, anecdotal evidence suggests that young Pacific male athletes face numerous factors that deter help-seeking behavior. In response, a mixed-methods study was carried out with young Pacific male athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…4 Similarly, in a subset of young Pasifika male athletes, friends and family were also preferred over professional help; with friends and teammates preferred over family. 23 Previous research has also identified Pasifika preference for less medicalised and individualised health services 24 ; however, it is possible that these alternative forms of support are due to the lack of cultural responsiveness in the current mental health system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Similarly, in a subset of young Pasifika male athletes, friends and family were also preferred over professional help; with friends and teammates preferred over family. 23 Previous research has also identified Pasifika preference for less medicalised and individualised health services 24 ; however, it is possible that these alternative forms of support are due to the lack of cultural responsiveness in the current mental health system.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study provide further evidence to support more Pasifika centred approaches to improving access to mental health services, especially for those in areas of highest deprivation. Such approaches may include assisting in increasing health literacy to support knowledge of where to get support for mental health, 4,23,30 and addressing practical issues such as lack of transport and language barriers known to contribute to low utilisation of healthcare services and under-diagnosis of some conditions. 31 Finally, it may be related to perceived stigma or other inhibitions towards help seeking behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] Somado a isso, ainda existe uma considerável resistência por parte destes atletas em procurar ajuda especializada com receio das consequências negativas, tanto para sua vida pessoal, como profissional. 34, 36 Relativamente aos atletas com idade mais avançada, e que muitas vezes já se encontram mais perto do fim da sua carreira desportiva, deve-se ter atenção para a maior probabilidade destes indivíduos desenvolverem sintomas e doenças mentais como ansiedade, depressão e abuso de álcool. 1, 37 A perda de rotina de treino e de competições, a falta de objetivos após a reforma desportiva, a falta de apoios, a alteração de estado social são alguns dos fatores de origem de stress que têm maior influência no aparecimento de sintomas e doença mental.…”
Section: Fatores Que Podem Influenciar O Aparecimento De Sintomas De ...unclassified